Design of an Android-based Letter Submission Application for Panjer Village - Akbar Surya Pamungkas (P3M Politeknik Negeri Bengkalis, 2024)
This study aims to show the existence of a problem that occurs in Kelurahan Panjer related to the submission of correspondence for villagers. The distance of the village head office makes access to the submission of letters hampered and even difficult to do. The methods used in this research include interviews with Panjer village residents, observation by looking directly at the field and using previous research as a comparison material. The purpose of this research is to speed up the process of submitting citizen letters and implementing the government's mandate on E-Government as a form of government responsibility to its citizens. The result of this research is a letter submission application with 6 types of letters that can be submitted. This research concludes that with this application, letter submission becomes faster because villagers do not need to come to the village office.